The capacity and innovation of services in organizing village governance in Indonesia - Kusumastuti, Henni; Alfi Haris Wanto, Bambang Supriyono, Lely Indah Mindarti, (Opción, 2020)
This article is going to discuss the capacity and innovation regarding the civic services of the Village Government via a descriptive qualitative research method. The results of the study show that the innovative capacity of Leadership, the Strengthening of Official Aspects, Human Resources, and the Management of Village Government are the factors that influence the management of innovation in public services in some of the villages in Southern Lampung district. In conclusion, there was an interaction with higher education academics as partners through the cooperation of the fostered village program and training of the village financial system.